Effects of Artificial Intelligence (AI) Platforms on Medical Education Among Medical Students in Majmaah University (Medical Forum Monthly, 2026)
Objective: To assess the effects of AI platforms on learning outcomes, study behavior, and academic performance among medical students at Majmaah University. Study Design: Descriptive cross-sectional study Place and Duration of Study: This study was conducted at the Majmaah University, Saudi Arabia from July 2025 to August 2025. Methods: This descriptive cross-sectional study included 510 medical students selected through non-probability sampling. Data were collected using a structured electronic questionnaire that assessed demographic characteristics, AI usage patterns, perceived educational benefits and challenges, and academic performance indicators.  Results: Most students (78%) used AI tools regularly, with ChatGPT being the most common platform. Higher usage frequency was strongly associated with better theoretical understanding (mean score 4.7 ± 0.5), enhanced clinical reasoning (4.4 ± 0.6), improved exam preparation efficiency (4.7 ± 0.5), and increased study motivation (4.2 ± 0.7). Students who used AI daily demonstrated significantly higher GPAs (3.78 ± 0.41) and greater improvement in test scores (18.4 ± 6.2%) than low users.  Conclusion: AI platforms substantially enhance medical students’ academic performance, conceptual understanding, and study efficiency; however, risks related to misinformation and dependency highlight the need for structured, ethical, and guided integration into medical education.